2011
DOI: 10.1212/wnl.0b013e3182343377
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of inappropriate antidiuresis may herald or accompany neuromyelitis optica

Abstract: HERALD OR ACCOMPANY NEUROMYELITIS OPTICAAquaporin-4 (AQP4) is the target autoantigen of an immunoglobulin G (IgG) autoantibody that distinguishes a spectrum of inflammatory demyelinating CNS disorders (the neuromyelitis optica [NMO] spectrum) from multiple sclerosis (MS) and other CNS demyelinating disorders. 1 Compelling evidence supports this IgG having a central role in the pathogenesis of NMO. AQP4 is concentrated in astrocytic foot processes at interfaces between CNS parenchyma and fluid compartments, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 6 publications
2
47
0
Order By: Relevance
“…Disease in CNS could start with the movement of AQP4-IgG from the periphery into the circumventricular organs, where blood-brain barriers might lack, such as the area postrema [20] and the posterior hypothalamus [24], …”
Section: E P T E Dmentioning
confidence: 99%
“…Disease in CNS could start with the movement of AQP4-IgG from the periphery into the circumventricular organs, where blood-brain barriers might lack, such as the area postrema [20] and the posterior hypothalamus [24], …”
Section: E P T E Dmentioning
confidence: 99%
“…Brain lesions are now a well-recognized feature of NMO (3), and the presence of "cloud-like" enhancement has been described as being specific for the disease (6). In particular, pathological (7), radiological (3) and clinical (8,9) studies have shown that brain sensory CVOs (the area postrema, organum vasculosum lamina terminalis and subfornical organ) are preferentially involved in NMO.…”
Section: Discussionmentioning
confidence: 99%
“…Both anorexia (4,5) and an increased appetite (11) associated with inflammatory lesions involving the area postrema or the hypothalamus have been described in NMO patients. Pathologic studies have revealed that inflammatory lesions of the area postrema are present in up to 40% of NMO patients (9). However, the subfornical organ and the organum vasculosum of the lamina terminalis have not yet been studied in patients with NMO.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothalamic lesions have been associated with disturbance of water and salt equilibrium [2]. Herein, we report a case of NMOSD associated with hyponatremia and osmotic demyelination syndrome (ODS).…”
Section: Introductionmentioning
confidence: 98%